2011
DOI: 10.1002/jpln.201000265
|View full text |Cite
|
Sign up to set email alerts
|

Contents and bioavailability of rare earth elements in agricultural soils in Hesse (Germany)

Abstract: With increasing agricultural and industrial use of rare earth elements (REEs), input of REEs into the pedosphere has risen in parallel. Since total REE budgets for soils in Germany are mainly unknown, this pilot study investigates the concentrations of REEs in three loess soil profiles under agricultural land use in the Wetterau region, Germany. There were no significant REE applications in the past, so the presented data can be considered as background concentrations of REEs in soils. In addition to the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 30 publications
5
20
0
Order By: Relevance
“…In the study of other horizons, especially in surface horizons, the contents of bioavailable fractions were found in low proportions. Also Loell et al (2011) found a similar tendency of the fractions of rare earth elements. The percentage sequences of the elements in t h e five fractions in diagnostic genetic horizons are presented in Table 4.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the study of other horizons, especially in surface horizons, the contents of bioavailable fractions were found in low proportions. Also Loell et al (2011) found a similar tendency of the fractions of rare earth elements. The percentage sequences of the elements in t h e five fractions in diagnostic genetic horizons are presented in Table 4.…”
Section: Discussionsupporting
confidence: 58%
“…The mean concentration of potentially bioavailable (∑F1-F2) REEs, extracted by 1M MgCl2, was for scandium and yttrium respectively: 0.05 and 1.10 mg kg -1 . Soil properties, such as low pH values, and low Corg contents, increase solubility of REEs (Loell et al, 2011, Tyler and Olsson 2005, Kabata-Pendias and Pendias, 1993, 1984. Accordingly, soil properties must be taken into account while studying the REEs' availability.…”
Section: Discussionmentioning
confidence: 99%
“…The water soluble and/or exchangeable fractions are commonly targeted for studying biogeochemical cycling (e.g. Drouet et al, 2007;Fang et al, 2007;Frei et al, 2009;Leybourne and Johannesson, 2008;Loell et al, 2011;Miller et al, 1993;Poszwa et al, 2000;Tyler, 2004) …”
Section: Estimating Element Bioavailability In Soilmentioning
confidence: 99%
“…Thus, despite the well-established complexities of REE chemistry in soils (e.g., reflecting a combination of host mineral effects, pH controls, complexation) (Byrne and Sholkovitz, 1996;Deberdt et al, 2002;Elderfield et al, 1990;Lawrence and Kamber, 2006;Matsunaga et al, 2015;Noack et al, 2014;Pédrot et al, 2015a;Tricca et al, 1999) originating from igneous rock, sandstone, and shale tending to have higher REE contents than soils developed from loess and calcareous rock (Hu et al, 2006;Loell et al, 2011). In general, the high REE in the basalt-dominated soil indicates the most easily leachable REE fraction, which likely reflects the lack of poorly leachable REErich phases and the high abundance of Fe/Mn-oxy(hydroxides) with potentially adsorbed REE.…”
Section: Translocation Of Ree+y From Soil To Biomassmentioning
confidence: 99%
See 1 more Smart Citation